Pengalaman Kepercayaan Merek, Keamanan, dan Perilaku Konsumen dalam Keputusan Pembelian: Studi Fenomenologi pada Ibu Rumah Tangga di Kota Bitung - Devie Mathilda Lumentut (Fakultas Ekonomi Universitas 45 Surabaya, 2025)
This study aims to explore the experiences of housewives in Bitung City related to brand trust, safety, and consumer behavior in making purchasing decisions. Using a qualitative phenomenological approach, this study explores an in-depth understanding of how aspects of brand trust and product safety perceptions influence consumer behavior in the context of everyday life. Data were collected through in-depth interviews with purposively selected participants to ensure the relevance of their experiences to the focus of the study. The results of the analysis indicate that brand trust plays an important role in building consumer loyalty, especially when the brand is able to meet quality expectations and provide a sense of security. In addition, the perception of product safety, especially household consumption products, is a major determining factor in making purchasing decisions. The findings also reveal that housewives tend to prioritize brands that have a good reputation and are transparent in providing product information. This study contributes to the literature on consumer behavior by highlighting the importance of brand trust and safety in shaping purchasing decisions, especially among housewives. These findings are expected to be a reference for manufacturers and marketers in designing more effective marketing strategies that focus on increasing product trust and safety.